EHealth technologies and the know-do gap: exploring the role of knowledge mobilisation. (1st November 2020) - Asthana, Sheena; Sheaff, Rod; Jones, Ray; Chatterjee, Arunangsu
Abstract : Background: eHealth technologies are widely believed to contribute to improving health and patients' experience of care and reducing health system costs. While many studies explore barriers to and facilitators of eHealth innovation, we lack understanding of how this knowledge can be translated into workable, practicable and properly resourced knowledge mobilisation (KM) strategies.Aims and objectives: This paper describes the aims, methods and outputs of a large European Union funded project (eHealth Productivity and Innovation in Cornwall and the Isles of Scilly (EPIC)) to support the development of a sustainable innovation ecosystem in Cornwall and the Isles of Scilly, in order to explore how knowledge mobilisation activities can help bridge the know-do gap in eHealth.Conclusions: Preparatory knowledge sharing, linkage making and capacity building are necessary preliminaries to co-production, with an emphasis on capturing the uses to which patients, carers and health workers want to put new technologies rather than promoting new technology for its own sake. Financial support can play a key role in supply-side dynamics, although the contextual and organisational barriers to eHealth innovation in England should not be underestimated.